Effect of artificial crowns on periodontal tissues (Literature Review): Pengaruh mahkota tiruan terhadap jaringan periodontal (Tinjauan Literatur) - Aisyah Bella Azzanjani; Dian Setiawati (Makassar Dental Journal PDGI Makassar, 2022)
Dental crowns are artificial teeth that are permanently attached to teeth that have been prepared to repair part or all of the damaged tooth surface and to replace toothloss. Making a crown must consider several factors, including being able to maintain and pro-tect existing teeth and surrounding tissues. This literature review isaimed to describe the effect of crown use on periodontal tis-sue. A total of 20 articles collected from various electronic databases and manual searches wereincluded in this literature. Plaque is a major etiologic factor of gingival inflammation and inadequate crown design can lead to plaque accumulation. Dental crowns can cause inflammation of the periodontal tissues, if cervical endings and preparation margins as well as oral hygiene principles are not observed during the crown fabrication process. It is concluded that crown design plays a very important role in determi-ning the condition of periodontal tissues. Appropriate designand good oral hygiene are important to reduce the occurrence of periodontal disease.